National Wage Setting - Jonathon Hazell; Christina Patterson; Heather Sarsons; Bledi Taska (Institute of Labor Economics (IZA), 2023)
How do firms set wages across space? Using job-level vacancy data and a survey of HR managers, we show that 40-50% of a job's posted wages are identical across locations within a firm. Moreover, nominal posted wages within the firm vary relatively little with local prices, a pattern we verify with other measures of job level wages. Using the co-movement of wage growth across establishments, we argue these patterns reflect national wage setting - a significant minority of firms choose to set the same nominal wage for a job across all their establishments, despite varying local labor market conditions.
Keywords: J24; J45; J33; H56; 330; national wage setting; labor markets